PENERAPAN PENANGGALAN JAWA DALAM PENENTUAN HARI AWAL BERCOCOK TANAM DI DESA NGRANGIN KABUPATEN MALANG - Muhamad Andre Nurdiansah; Icha Adelia Safinka Artamefina (An Natiq, 2023)
In Indonesia, especially the majority of Javanese people, still believe in traditions that have been passed down from their ancestors, One of the legacies is the Javanese Count, one of which is Pranata Mangsa, which is still carried out by farmers in Ngrangin Village, Sumber pasir, Pakis, Malang. There is one thing that is interesting in this study, namely the farming activities in Ngrangin Village. When the farmers are about to plant, they use the Pranata Mangsa tradition to determine an auspicious day to start farming. The research method used this time is a qualitative research method with observation and interview techniques to collect data. The farmers of Ngrangin Village still apply Javanese calculations because this tradition needs to be preserved because they think that if this tradition is not carried out, unwanted things will happen, such as crop failure. This is also a form of respect for their ancestors, so this will strengthen the trust of the people of Ngrangin Village and maintain this tradition. In Ngrangin Village, the farming process does not have to be completed on that day, only the planting process. The people of Ngrangin Village also celebrate, which is a form of expression of gratitude to Allah SWT.